Cover. Issue 3 (15th March 2022) - Ito, Shin; Hashimoto, Aya; Yamaguchi, Kazunori; Kawamura, Sadafumi; Myoen, Shingo; Ogawa, Maki; Sato, Ikuro; Minato, Takamichi; Miyabe, Shingo; Nakazato, Akira; Fujii, Keitaro; Mochizuki, Mai; et al.
Abstract : The cover image is based on the Original Article A novel 8.57‐kb deletion of the upstream region of PRKAR1A in a family with Carney complex by Shin Ito et al., https://doi.org/10.1002/mgg3.1884 .